Assuming you want us to answer question 12.
11x - 7y = -14
x - 2y = -4
From the second equation, you can find x by adding 2y to both sides.
x = 2y - 4
Now that you've found what x is, go back to the first equation 11x - 7y = - 14
But now, wherever you see x in this, substitute in what you found for x.
Our value for x is 2y - 4.
11(2y - 4) - 7y = -14
Expand and simplify
22y - 44 - 7y = -14
15y - 44 = -14
15y = 30
y = 30/15 = 2
Now we know what y is, lets find x as a number.
Use what we found as x to find it as a number (x = 2y - 4), but substituting in 2 wherever we see 'y'.
So x = 2(2) - 4
= 4 - 4 = 0
So x = 0 and y = 2